2016
DOI: 10.1177/0149206316633268
|View full text |Cite
|
Sign up to set email alerts
|

Organizations Driving Positive Social Change

Abstract: Academic and practitioner interest in how market-based organizations can drive positive social change (PSC) is steadily growing. This paper helps to recast how organizations relate to society. It integrates research on projects stimulating PSC-the transformational processes to advance societal well-being-that is fragmented across different streams of research in management andAcknowledgments: The second and third authors contributed equally to this manuscript. The authors are grateful for the excellent friendl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(131 citation statements)
references
References 160 publications
2
112
0
1
Order By: Relevance
“…Charlier et al (2016) found that many companies have changed to e-learning programs and relied on the employees to train themselves. Moreover, the findings aligned with Stephan et al (2016), who revealed that managers who motivate, train, and encourage employees improve organizational productivity.…”
Section: Theme 3: Training Improved Employee Performancesupporting
confidence: 76%
See 3 more Smart Citations
“…Charlier et al (2016) found that many companies have changed to e-learning programs and relied on the employees to train themselves. Moreover, the findings aligned with Stephan et al (2016), who revealed that managers who motivate, train, and encourage employees improve organizational productivity.…”
Section: Theme 3: Training Improved Employee Performancesupporting
confidence: 76%
“…Successful businesses create opportunities that can bring positive social change to the communities they serve (Crane, Palazzo, Spence, & Matten, 2014). Organizations can bring positive social change in many ways, such as motivating and training community members, receiving input on projects for improvements, and creating new employment (Stephan, Patterson, Kelly, & Mair, 2016). Employee disengagement threatens organizational profitability and productivity (Hollis, 2015) and affects companies' ability to contribute to their communities.…”
Section: Implications For Social Changementioning
confidence: 99%
See 2 more Smart Citations
“…1 In doing so, they influence the lives of their employees and indirectly touch the lives of citizens who are often involuntarily exposed to the consequences of organizations' actions (e.g., environmental pollution). Yet organizations can also play a positive role in society from promoting healthy eating to aiding poverty alleviation (Stephan, Patterson, Kelly, & Mair, 2016). The values of strategic leaders appear to play an important role in pursuing such courses of action.…”
Section: Introductionmentioning
confidence: 99%